The Effect of Bankruptcy Possibility on Audit Delay and Timeliness (Empirical Study on Manufacturing Companies Listed in Indonesian Stock Exchange in the Period of 2012-2016) - Meinarsih, Triana; Yusuf, Abdul; Hamzah, Muhammad Zilal (Universitas Agung Podomoro, 2018)
Audit delay and timeliness are important factors that influence the quality of accounting information interm of relevance. This study provides empirical evidence to answer the question of how bankruptcypossibility impacts on audit delay and timeliness. This research studies manufacturing firms listed inIndonesian Stock Exchange (IDX) in the period of 2012-2016. Data are taken from official website ofIDX. This study is a quantitative research that seek to find out relationship between independentvariable and dependent variable. External secondary data used are annual reports accessed from IDXwebsite. Measurement used is Z-Score Altman model prediction, while simple linear regression isemployed as technical analysis. This study finds that bankruptcy possibility which is measured by Z-Score is negatively influence audit delay and timeliness. Any decrease of Z-Score shows the possibilityof a company experience bankruptcy and therefore causes audit delay and timeliness.